Platinum and indium sulfide-modified Cu3BiS3 photocathode for photoelectrochemical hydrogen evolution. Issue 21 (15th May 2017) - Kamimura, Sunao; Beppu, Naoki; Sasaki, Yousuke; Tsubota, Toshiki; Ohno, Teruhisa
Abstract : Platinum-deposited In2 S3 /Cu3 BiS3 film as a photoelectrode was fabricated on a molybdenum-coated glass substrate for photoelectrochemical hydrogen evolution. Abstract : A polycrystalline Cu3 BiS3 film as a photoelectrode was fabricated by an electrodeposition method on a molybdenum-coated glass substrate for photoelectrochemical hydrogen evolution. The Cu3 BiS3 film was composed of dense crystallites with thicknesses of ca. 0.65 μm, and the optical bandgap was estimated to be ca. 1.6 eV. Photoelectrochemical characterization revealed that the Cu3 BiS3 film was a p-type semiconductor with a flat band potential of ca. +0.1 V ( vs. Ag/AgCl at pH 6), which is suitable for water reduction but cannot be used for water oxidation. Deposition of an In2 S3 buffer layer, by which effective contact between p-type Cu3 BiS3 and n-type In2 S3 was formed, resulted in a significant increase in the photocurrent and a large shift of the photocurrent onset to the positive region. H2 evolution under AM 1.5G simulated solar light was demonstrated using the Pt–In2 S3 /Cu3 BiS3 electrode combined with a Pt electrode under an applied bias (0 V vs. RHE).